AB0152 Evaluation of Semaphorine 3A, Sclerostin and Bone Morphogenic Protein 2 in Patients with Axial Spondyloarthritis. (9th June 2015) - Perrotta, F.M.; Ceccarelli, F.; Spinelli, F.; Montepaone, M.; Colasanti, T.; Barbati, C.; Valesini, G.
Abstract : Background: Mechanism of new bone formation in axial Spondyloarthritis (axSpA) is still not fully understood. Signal pathways implicated in bone metabolism such as semaphorins/NP-1, Wnt/beta-catenin, bone morphogenic proteins and RANK/RANKL system seems to be associated with radiographic progression of the disease and potentially target for the therapy. Objectives: The aim of the study was to assess serum levels of semaphorine 3A (SEMA 3A), sclerostin and bone morphogenic protein 2 (BMP-2) in patients with axSpA and to assess the relationship with disease activity parameters and radiological index of damage. Methods: Consecutive patients with axSpA fulfilling ASAS criteria and 20 age and sex-matched healthy controls were enrolled. Ankylosing Spondylitis Disease Activity Score-C reactive protein (ASDAS-CRP), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) were used as additional disease activity measures. Bath Ankylosing Spondylitis Metrology Index (BASMI) was used to assess spinal mobility. Lateral spine radiographs, collected within 6 months, were scored by using the modified Ankylosing Spondylitis Spine Score (mSASSS) for chronic axSpA-related changes. Serum level of SEMA 3A, sclerostin and BMP-2 were evaluated using commercial ELISA kit in all patients and controls. Results: We enrolled 20 axSpA patients [M/F: 14/6; age (median/25°-75° percentile) 50.5/40.5-54.75 years; disease duration (median/25°-75° percentile) 11/6.75-20 years]. Sclerostin serum levels were significantly lower in axial SpA patients compared to healthy control (p=0.002); serum levels of SEMA 3A and BMP-2 did not statistically differ among patients and controls. Moreover SEMA 3A serum levels showed a positive correlation with mSASSS (rho 0.41; p=0.04) and a negative correlation with ESR (rho -0.44; p=0.04). We did not find any correlations between serum levels of BMP-2 and disease activity and disability indices. Conclusions: Our pilot study showed that serum levels of sclerostin, an inhibitor of bone formation through Wnt/beta-catenin pathway, were low in patients with axSpA, according to previous studies. Moreover, the correlation of SEMA 3A serum levels with radiographic damage corroborate the hypothesis that these proteins, and the relative pathways, could be implicated in new bone formation in axSpA. Disclosure of Interest: None declared